FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS (Studi Empiris Pada Perusahaan Manufaktur Periode 2014-2016) - Patricia Gladys Perdianti, 14.05.52.0040; Nurhayati, Ida (Students' Journal of Accounting and Banking, 2018)
This study aims to empirically examine the effect of cash trunover, receivable turnover, inventory turnover, firm size, leverage, liquidity on profitability. The total population of this study 159 and a sample of 278 manufacturing companies listed on the Indonesia Stock Exchange for the period 2014-2016 by using purposive sampling method. The analysis regression test, model test and hypothesis test. Based on the research that has been done, the results of this study indicate that intentory turnover, frim size and liquidity have a significant positive effect on profitability. While cash turnover, receivable turnover and leverage have no significant effect on profitability. Keywords: Cash Turnover, Receivable Turnover, Inventory Turnover, Firm Size, Leverage, Liquidity and Profitability